Playbuilding as reflexive practice: Exploring implicit bias through participatory theatre - Metz, Michael; Ganesh, Nadia; Hobbs, Kevin (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
Implicit bias education in the health sciences is crucial for disrupting the individual and systemic oppressive values that contribute to inequitable access to healthcare. In short, implicit bias can kill. Through a Playbuilding approach, dramatic vignettes on implicit bias were shown to undergraduate health science students in a performance workshop entitled Haunting our Biases: Using Participatory Theatre to Interrupt Implicit Bias. Through Forum Theatre, the vignettes were explored, discussed, and re-made. Three project members reflect on their roles, discussing Playbuilding, pedagogical potential, and the process of developing assessments of the project’s efficacy. Conclusions are offered on the reflexive impact of the Playbuilding process and the potential for growth, for both researchers and participants, that can emanate from such work.